A framework for physician assistant intervention for overweight and obesity. Issue 7 (July 2015) - Herman, Lawrence; McGinnity, John G.; Doll, Michael; Peterson, Eric D.; Russell, Amanda; Largay, Joseph
<x xml:space="preserve">Abstract</x> Abstract Overweight and obesity compose a chronic disease process of epidemic proportions that presents on a continuum, likely affecting nearly two out of every three patients treated by physician assistants (PAs). However, meaningful and actionable definitions, including but not limited to anthropometric and clinical descriptors, are needed. The effective treatment of overweight and obesity requires an efficient and timely process of screening, diagnosis, evaluation of complications, staging, and clear algorithmic management. PAs are trained as primary care providers and can diagnose and treat overweight and obese patients regardless of practice setting and across the spectrum of the disease and patient's age.